2015
DOI: 10.1007/s12035-015-9380-2
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride-Induced Neuron Apoptosis and Expressions of Inflammatory Factors by Activating Microglia in Rat Brain

Abstract: Excessive exposure to fluoride results in structural and functional damages to the central nervous system (CNS), and neurotoxicity of fluoride may be associated with neurodegenerative changes. Chronic microglial activation appears to cause neuronal damage through producing proinflammatory cytokines and is involved in many neurodegenerative disorders. It is not known about effects on microglia of fluoride. In the present study, healthy adult Wistar rats were exposed to 60 and 120 ppm fluoride in drinking water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 47 publications
(53 reference statements)
5
43
0
Order By: Relevance
“…Recent studies have suggested that neuroinflammation is accompanied by the activation of microglial cells and the release of inflammatory mediators, which activates cellular cascades and results in neural apoptosis in the brain [47,48] . Our results indicate that SalB blocks the CMS-induced increases in apoptosis in both the hippocampus and cortex and prevents the decrease of hippocampal volume and cell density.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that neuroinflammation is accompanied by the activation of microglial cells and the release of inflammatory mediators, which activates cellular cascades and results in neural apoptosis in the brain [47,48] . Our results indicate that SalB blocks the CMS-induced increases in apoptosis in both the hippocampus and cortex and prevents the decrease of hippocampal volume and cell density.…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines are responsible for the initiation of inflammatory states and the death of neurons [59]. Research shows that the exposure of adult rats to fluorine causes the activation of microglia in the hippocampus and cerebral cortex and that it initiates an inflammatory state through the synthesis of proinflammatory cytokines—Il-1B, Il-6 and TNF-α (the concentration in drinking water, 60 and 120 mg/L) [60]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, among adult rats supplied with fluorine in drinking water, there was an increased expression of the proapoptotic protein Bax and a decreased expression of the apoptosis inhibiting Bcl-2. The analysis carried out by means of the terminal deoxynucleotidyl transferase dUTP nick end labelling (TUNEL) method confirmed the increased intensity of apoptotic processes in brain structures of the animals (the concentration in drinking water, 60 and 120 mg/L) [60]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations